PERAN ORANG TUA DALAM MENINGKATKAN HAFALAN AL-QURAN SISWA - Haya Syatina; Junias Zulfahmi; Maya Agustina (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
The role of parents in education is a direct action to supervise, control and evaluate every child's activity. For children's education to be better, parents must act as educators who can set an example for children. This research is field research with a qualitative descriptive method. Data collection was carried out through interviews, observation, and documentation. The results showed that: (1) Parents act as example providers and command to imitate, parents also provide duties and responsibilities, parents provide opportunities to try, parents conduct supervision and checks on children's education and parents provide motivational encouragement. (2) The driving factor for parents in improving the memorization of the Qur'an, namely, yearning for children who are righteous and righteous, wanting to achieve the targets set by the school, the ability of parents to read the Qur'an, and environmental factors at home. and a conducive society. While the inhibiting factor for parents in improving memorization of the Qur'an is psychological factors, which arise from oneself, such as passivity. In addition, social environmental factors can also affect children, the lack of ability and understanding of parents towards the Qur'an, and parents are busy at work.